Analisis Penanganan Kerusakan Pada Ruas Jalan Desa Laala-Olas Kabupaten Seram Bagian Barat - Gersom Herman Reasoa; Renny James Betaubun; Elisabeth Talakua (KOLONI, 2024)
Handling damage to the Laala-Olas village road section is by conducting a topographic survey and planning drainage channels. Where topography is a branch of science that focuses on examining the land surface and natural appearance of the earth's culture. The results of topographic studies are in the form of three-dimensional images or photographs, the output of which describes the relief of the high and low surface of the earth, the shape of the area, the slope of the earth, the object of the slope of the mountains, and others. Drainage itself is one of the elements of public infrastructure that people need in order to have a safe, comfortable, clean and healthy life. Its presence is very important for an area, especially residential areas and highways. This research method is carried out directly at the research location to obtain existig data directly from the field and literature research. the author uses the terrestrial method for topographic measurements and the rational method for planning drainage channels at the research location. From the topographic measurement data, the elevation of the new road body is planned at STA 0+000 - STA 0+850 by 60 cm from the original road body, at STA 2+650 - STA 4+750 and STA 4+900 - 6+000 by 40cm from the original road body. Then in the calculation of excavation and embankment, the excavation volume is 8403,62m3 and the embankment volume is 26960,94m3. in the planning of drainage channel dimensions for a 10-year return period, the peak width of the channel is 90cm, the width of the channel base is 55cm, and the channel depth is 75cm